Neural reactivity parameters of awareness predetermine one-year survival in patients with disorders of consciousness. (21st March 2021) - Meiron, Oded; Barron, Jeremy; David, Jonathan; Jaul, Efraim
ABSTRACT: Objective : The current investigation evaluated the sensitivity of neural-reactivity markers of awareness versus standard clinical assessments in predicting 1-year survival in nonresponsive-awake patients with disorders of consciousness (DOC). Methods: Pre-attentive auditory mismatch-negativity (MMN) event-related potentials (ERP's), globally induced electroencephalography (EEG) spectral power following verbal command, and clinical parameters were assessed. The study included 10 patients with DOC with mixed etiology and 10 healthy controls (HC) at baseline. The clinical status of patients with DOC was reassessed after 1 year. Results: Unlike baseline clinical assessment scores, baseline MMN amplitudes of non-survivors and induced theta-power following verbal-command clearly distinguished the non-surviving patients versus surviving patients. Baseline MMN peak-amplitude latencies in survivors with DOC were significantly related to clinical outcome over a 1-year period. Conclusion: Current findings underscore the increased sensitivity of EEG-reactivity markers of awareness versus standard clinical scores in predicting 1-year clinical outcome and survival in patients with DOC. Further longitudinal research in larger DOC samples is needed to confirm the prognostic-reliability, and validity of neural reactivity parameters of awareness in patients with DOC. Current finding may have implications for clinical care and medical–legal decisions in unresponsive-awake patients, and could assist clinicians to predict their survival up to 1 year from admission.